Desenvolvimento de plano terapêutico para modulação da dor lombar utilizando a Estimulação Transcraniana por Corrente Contínua - Souza, Marília Amorim de (2019)
Lumbar pain is characterized as pain or discomfort placed under the twelfth rib and above the inferior gluteal fold, being considered one of the most frequent causes of incapacities and morbidities in the general population. Due to its high rates of incidence, physiotherapy becomes an important indication to the treatment of this pathology. Thus, the Transcranial Direct-Current Stimulation (tDCS) stands out as an alternative and non invasive therapy modality to the relive of lumbar pains. In this context, the current study proposes the development of a therapy plan to the modulation of lumbar pain using the Transcranial Direct-Current Stimulation. 32 individuals, with the diagnostic of lumbar pain, with ages between 18 and 31, have been recruited, they have been allocated into two groups, experimental and control, both groups have received a booklet with specific exercises for the lumbar region, with the objective of performing them once a day through five consecutive days, however the experimental group has also done the treatment with tDCS (2 mA during 20 minutes for 5 days). For the data collecting have been used: McGill’s questionnaire, the Pressure Pain Threshold (PPT), the Motor Threshold (MT) through the Transcranial Magnetic Stimulation (TMS). As a result, there was an improvement in the pain sensation referred by the volunteers, evaluated through McGill’s questionnaire, when comparing the final evaluations of both groups, the value was statistically significative (p < 0,05). In relation to the PPT of the lumbar square muscle, only the experimental group has obtained an increase in the average post-treatment. In the pollicis adductor MT, only the experimental group has reached a favorable result, nonetheless, the statistic value has been significative (p=0,003376). Therefore, parting from the presented data, the usage of non-invasive brain stimulation through tDCS stands as a potential tool capable of promoting neuromodulation of pain in individuals with lumbar pain.